La « pacification » et ses rumeurs : les incidences des Unités de Police Pacificatrices sur les problèmes publics dans les favelas de Rio de Janeiro - Palloma Valle Menezes (Confins)
This paper focuses on rumors that have been circulating in the favelas of Santa Marta and City of God since November 2008, when police occupied these favelas where were launched later the two first Pacifying Police Units in the city of Rio de Janeiro. In this paper, I suggest that analyzing these “improvised news” may help to understand the changes in concerns and public problems that affect the routines of “pacified” favelas residents in the last five years. This reflection is based on an ethnographic research conducted in Santa Marta since 2009 and in the City of God since 2012.